Multiple-input single-output current-mode multifunction filter using current differencing transconductance amplifiers - Tangsrirat, Worapong; Dumawipata, Teerasilapa; Surakampontorn, Wanlop (My University, 2007)
A novel current-controlled multiple-input single-output current-mode universal filter employing current differencing transconductance amplifiers (CDTAs) as active elements is described. The proposed circuit offers the following attractive features: employment of the minimum number of active and passive components; simultaneous realization of all the standard filtering functions; independent current-control of the parameters ωo and ωo / Q; no requirement of component matching conditions; employment of only two grounded passive capacitors which is suitable for integrated circuit (IC) implementation; and low passive and active sensitivities. PSPICE simulation results are given to verify the theoretical analysis. An example application using the proposed circuit in cascade realization of the high-order current-mode filter is also presented. © 2006 Elsevier GmbH. All rights reserved.
Keywords: Current differencing buffered amplifier (CDBA); Current differencing transconductance amplifier (CDTA); Current-mode circuits; Multifunction filter